2023
DOI: 10.1097/hcr.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation for Post-COVID-19

Abstract: Purpose: Patients with COVID-19 often report persistent respiratory symptoms. Limited data exist on how to mitigate long-term sequelae of exercise intolerance and dyspnea. We aimed to study the role of pulmonary rehabilitation (PR) in patients with post-COVID-19. Methods: This was an observational study. Consecutive patients with post-COVID-19, admitted to three separate outpatient PR programs, were enrolled. The program consisted of 8-12 wk of PR sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Pulmonary rehabilitation showed a promising positive effect on long COVID patients. 49 , 50 A Systematic Review and Meta‐Analysis showed that pulmonary rehabilitation could improve exercise capacity measured by 6MWD among patients with mild‐to‐moderate lung impairment after COVID‐19. 51 In patients with long COVID, exercise capacity, functional status, dyspnoea, fatigue and quality of life improved after 6 weeks of personalized interdisciplinary pulmonary rehabilitation.…”
Section: Role Of Pulmonary Rehabilitation In Long Covidmentioning
confidence: 99%
“…Pulmonary rehabilitation showed a promising positive effect on long COVID patients. 49 , 50 A Systematic Review and Meta‐Analysis showed that pulmonary rehabilitation could improve exercise capacity measured by 6MWD among patients with mild‐to‐moderate lung impairment after COVID‐19. 51 In patients with long COVID, exercise capacity, functional status, dyspnoea, fatigue and quality of life improved after 6 weeks of personalized interdisciplinary pulmonary rehabilitation.…”
Section: Role Of Pulmonary Rehabilitation In Long Covidmentioning
confidence: 99%